ANALISIS IMPLEMENTASI LAYANAN E-PUSKESMAS PADA PUSAT KESEHATAN MASYARAKAT DI KECAMATAN AIR KUMBANG KABUPATEN BANYUASIN - Helda Fitriani (Jurnal Public Administration, Business and Rural Development Planning, 2023)
This study aims to find out how the implementation of E-Puskesmas Services at Community Health Centers in Air Kumbang District, Banyuasin Regency. As for the population of this study were the employees of the Cinta Manis Community Health Center, totaling 12 people. Adhering to the principle of rationality and to support the validity of the research results, the number of samples was determined, namely from employees as many as 12 people from the total population purposively. Types and sources of data collected include primary data, namely data obtained directly from research respondents, while secondary data is a source of data and information as well as information from agencies related to this research. The implementation theory that the writer uses is according to George Edward III. Whereas Implementation is an activity of administrative activities as an institution intended as one of the process activities carried out by administrative units or bureaucratic units. In the approach theorized by Edward III, there are 4 variable indicators that greatly determine the success of implementation, namely: Communication, Resources, Disposition and Bureaucratic Structure. To obtain more valid data and information, the data collection techniques used were questionnaires, observations and interviews. This research is in the form of a descriptive survey, namely by drawing a number of samples from the existing population, prioritizing research aids in the form of questionnaires so that the data is expected to be able to answer the desired research. As for the results of the research on how the implementation of E-Puskesmas Services at Community Health Centers in Air Kumbang District, Banyuasin Regency was assessed as